Evolución de Schramm-Loewner - Maura Llauri, Christian Jaime (2020)
The Schramm-Loewner Evolution, or SLE, is a chain of random compact sets that allows us to generate any random curve that satis es conformal invariance as well as the domain Markov property. Its construction goes through the solution of a random version of Loewner's deterministic equation: @tgt(z) = 2 gt(z) f(t) g0(z) = z where the continuous function f is replaced by a stochastic process p kB, where k is a positive constant and B a Brownian motion. This construction enables the inclusion of stochastic calculus tools in the study of the curves generated by the SLE. The main objective of this thesis is to provide an accessible and introductory description of SLE. To do this, Loewner's theorems, which allows us to establish bijections between families of hulls and families of biholomorphisms properly normalized in 1, as well as between real continuous functions of real variable and families of hulls, are enunciated and demonstrated. On these bijections, the good de nition of the SLE is justi ed as a random family of hulls with law induced by a Brownian motion through the Loewner random equation. Then some elementary properties that the SLE inherits from the Brownian movement are presented and the existence of the curve that generates the SLE is demonstrated. Finally, as a way of discussing the non-trivial character of the constant k that appears in front of the Brownian motion that gives rise to the SLE, a demonstration of a phase transition exhibited by the SLE curves is presented, which pass from curves simple to non-simple once you go from k 2 (0:4] to k > 4.